1992
DOI: 10.1128/aem.58.3.976-983.1992
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 1,2-dichloroethane by Ancylobacter aquaticus and other facultative methylotrophs

Abstract: Cultures of the newly isolated bacterial strains AD20, AD25, and AD27, identified as strains ofAncylobacter aquaticus, were capable of growth on 1,2-dichloroethane (DCE) as the sole carbon and energy source. These strains, as well as two other new DCE utilizers, were facultative methylotrophs and were also able to grow on 2-chloroethanol, chloroacetate, and 2-chloropropionate. In all strains tested, DCE was degraded by initial hydrolytic dehalogenation to 2-chloroethanol, followed by oxidation by a phenazine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 38 publications
(41 reference statements)
1
87
0
Order By: Relevance
“…39 Xanthobacteraceae, a third VOC-favored family, consisted mostly of Ancylobacter, a facultative methylotroph capable of using organochlorines as the sole carbon and energy source. 40 Very little is known about the potential VOC-degrading bacteria in green wall settings. Russell et al 21 -to our knowledge the only earlier comparable (ie cultivation-independent) green wall study-identified Hyphomicrobium as a rhizosphere-associated genus that responded positively to both exposure to VOCs as well as to growth/maturation of the plants.…”
Section: Identification Of Potentially Vocutilizing Bacteriamentioning
confidence: 99%
“…39 Xanthobacteraceae, a third VOC-favored family, consisted mostly of Ancylobacter, a facultative methylotroph capable of using organochlorines as the sole carbon and energy source. 40 Very little is known about the potential VOC-degrading bacteria in green wall settings. Russell et al 21 -to our knowledge the only earlier comparable (ie cultivation-independent) green wall study-identified Hyphomicrobium as a rhizosphere-associated genus that responded positively to both exposure to VOCs as well as to growth/maturation of the plants.…”
Section: Identification Of Potentially Vocutilizing Bacteriamentioning
confidence: 99%
“…To date, under aerobic conditions, 1,2-DCA is thought to be biodegraded via enzymatically initiated hydrolytic dehalogenation (C-Cl bond cleavage) or oxidation (C-H bond cleavage) reactions ( Fig. 1) (Janssen et al, 1985;Van Den Wijngaard et al, 1992;Hage and Hartmans, 1999). Under anaerobic conditions, 1,2-DCA biodegradation via a reductive dechlorination reaction (C-Cl bond cleavage), dihaloelimination reaction (cleavage of two C-Cl bonds and formation of a C=C double bond) and mineralization to CO 2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…DM2 [9][10][11] Pseudomonas sp. P4 [12] Xanthobacter autotrophicus [ 13] Ancylobacter aquaticus [ 14] Xanthobacter autotrophicus [ 13] Pseudornonas sp. ES-2 [ 15,16] Arthrobacter sp.…”
Section: 2-dichloroethanementioning
confidence: 99%
“…3). Both in X. autotrophicus GJ10 and Ancylobacter aquaticus, this involves two specific dehalogenating enzymes, encoded by the dhlA and dhlB genes, which have been cloned and sequenced [6,14,63]. The conversion of chloroacetate proceeds by a chromosomally encoded chloroacetate dehalogenase, that in fact belongs to the L-specific haloacid dehalogenases, as discussed above.…”
Section: Degradation Of 12-dichloroethanementioning
confidence: 99%